2018
DOI: 10.29244/jcds.3.1.28-43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parenting Style, Self-Efficacy, and Self Regulated Learning on Adolescents’ Academic Achievement

Abstract: <p>Academic achievement as one of learning outcome indicator in adolescents influenced by the self and family environment factors. This study was aimed to analyze the effect of child characteristics, family characteristics, parenting style perceived by adolescents, self-efficacy and self regulated learning on adolescents academic achievement. The study used self report method which involved 91 eighth grade students from two junior high schools in Bogor. Data analysis included descriptive analysis and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 9 publications
1
19
0
5
Order By: Relevance
“…Parenting self-efficacy is a belief that one can successfully parent a child, which affects one's willingness to take on the role of their child's first teacher (Elizabeth et al, 2017). This aspect consists of intrinsic learning motivation and parent involvement in learning, discipline, togetherness with parents, emotional and physical demands, learning pattern and facility, caring, and exhibit positive attitudes (Yang et al, 2018;Ningrum, 2016;Coleman & Karraker, 2008;Theresya et al, 2018;Young & Young, 2011) and describe related concepts such as self-concept of ability and parental competence (Whyte, 2015). Parent-child interactions, responsiveness, and parental involvement (Hughes, 2019).…”
Section: Problem Of Researchmentioning
confidence: 99%
“…Parenting self-efficacy is a belief that one can successfully parent a child, which affects one's willingness to take on the role of their child's first teacher (Elizabeth et al, 2017). This aspect consists of intrinsic learning motivation and parent involvement in learning, discipline, togetherness with parents, emotional and physical demands, learning pattern and facility, caring, and exhibit positive attitudes (Yang et al, 2018;Ningrum, 2016;Coleman & Karraker, 2008;Theresya et al, 2018;Young & Young, 2011) and describe related concepts such as self-concept of ability and parental competence (Whyte, 2015). Parent-child interactions, responsiveness, and parental involvement (Hughes, 2019).…”
Section: Problem Of Researchmentioning
confidence: 99%
“…The results of Situmorang and Latifah (2014) research also showed the effect of parental education on self-regulation strategies in learning. Meanwhile, the results of Theresya, Latifah, and Hernawati (2018) research showed that fathers education influenced adolescent academic achievement. The results of Stull's research (2013) show the effect of parents' socioeconomic status (SES) on children's learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The main education obtained by children comes from the family, the child first gets a stimulus in the family environment and the most time is spent by the child also in the family. The family environment provides learning patterns and facilities in the form of parenting style (Theresya, Melly, & Neti, 2018). The style of nurture studied extensively for human development begins in childhood (Kordi, 2010).…”
Section:  Introductionmentioning
confidence: 99%